Efeito do envelhecimento e da dose energética na fotobiomodulação laser de baixa intensidade na regeneração tendínea - Taciro, Charles (Universidade Federal de São Carlos, 2007)
There is a rapid increase in the size of the elderly population due to a complex interaction of medical and epidemiological factors. Also, there is a parallel increase in morbidity associated with age-related delayed tendinopathy healing, and treatment of such acute and chronic condition costs the Health Services over 1 Billion dollars per year. Despite the obvious clinical impact, the basic cellular and molecular mechanisms underlying impaired human tendon healing are largely unknown. However, recent reports have showed the action mechanism of low level laser therapy (LLLT) in producing accelerated tendon healing, but the real effects of this therapy associated with aging effects are not yet known. This study evaluated the effects of the LLLT on repair process of rat calcaneal tendon in two different ages. Eighty male Wistar rats were divided in 2 experimental groups with 40 rats at each one: young group (4 weeks old, body mass = 111.3±34,3g) and mature adult group (27 weeks old, body mass = 385.4±34,3g). The young group was subdivided in subgroup Y3J (12 session, total energy = 101.7mJ, laser 685nm, 5.4W/cm2, 3J/cm2), subgroup Y10J (12 session, total energy = 339.6mJ, laser 685nm, 5.4W/cm2, 10J/cm2); subgroup YPL (placebo treatment) and subgroup YCL (no treatment). The mature adult group was subdivided in subgroup A3J (12 session, total energy = 101.7mJ, laser 685nm, 5.4W/cm2, 3J/cm2), subgroup A10J (12 session, total energy = 339.6mJ, laser 685nm, 5.4W/cm2, 10J/cm2); subgroup APL (placebo treatment) and subgroup ACL (no treatment). All animals had the medial region of right calcaneal tendon totally tenotomized. They were sacrified on the 13th post-operate day and their tendons were surgically removed for a quantitative and qualitative analysis The Atomic Force Microscopy analysis showed better organization quality (alignment, thickness and aggregation) of collagen bounds in mature irradiated groups. However, it was found differences (p < 0.05) in thickness of collagen bundles (TCBs) for several intersections among subgroups. The subgroup A10J presented greatest TCBs (5.69±0.69), and the ACL subgroup presented smallest TCBs (4.51±0.6) in the mature group. The dimensional data showed higher differences in the irradiated subgroup in mature group when compared to the same subgroup in young group. Histological analysis showed increase (p < 0.05) in the number of capillar vessels and fibroblast cell proliferation after LLLT in both young and mature groups, however the higher modulation was observed in the mature group. Minor influence of laser radiation in the young group may be justified by divergence on chemistry, physics and metabolic age-related. Maybe the accumulated oxidative stress resulting from a gradual shift in the redox status of tissues should be a key mechanism underlying the aging process and the higher laser effect noted in the mature group. Age should be considerated an important parameter to LLLT.
Keywords: Fisioterapia; Laserterapia; Envelhecimento; Tendão de Aquiles; Reparo tecidual; Laser therapy; Tendon repair; Fibroblast; Blood vessel; Aging; Collagen; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL